Groundwater Extraction in Floodplain Forests Reduces Radial Growth and Increases Summer Drought Sensitivity of Pedunculate Oak Trees (Quercus robur L.) - Skiadaresis, Georgios; Schwarz, Julia A.; Bauhus, Jürgen (Frontiers in Forests and Global Change, 2019)
In future, groundwater dependent ecosystems are likely to face increasing stress from direct and indirect effects of climate change. European floodplain forests already experience lower groundwater tables caused by river regulations and water extraction. Yet, the effects of more frequent and prolonged dry and hot periods in combination with groundwater extraction on floodplain forests are not well understood. Here, we conducted a dendroecological study in floodplain forests dominated by pedunculate oak (Quercus robur), a widespread forest type in Europe. Since drought-related precipitation deficits are increasingly less compensated by available groundwater, we hypothesized that groundwater extraction would increase climate sensitivity of growth. Moreover, we expected that younger trees that established under the condition of lowered groundwater tables would be less sensitive to droughts in contrast to older trees that might not be able to adapt to abrupt changes in groundwater levels. In three regions in the Upper Rhine Valley of Germany, we analysed retrospectively tree-ring growth in Q. robur stands where (a) water extraction had dramatically lowered groundwater levels and trees presumably lost direct access to it, or (b) trees have not been affected by water extraction. In addition, (c) nearby sessile oak (Q. petraea) stands at upland sites were analysed to isolate the climate signal for each study region from a groundwater signal. In total, we analysed ring-width chronologies from 18 forest stands and investigated their relationship with climate. Radial growth of oak trees was strongly correlated with summer drought (SPEI, Standardized Precipitation Evapotranspiration Index). Their sensitivity to summer drought increased significantly following the onset of groundwater extraction (88-49 years ago). However, sensitivity of oaks to summer drought at sites with groundwater contact remained relatively stable over time. Oaks at sites without water extraction took advantage of favourable growing conditions. Our results show that access to groundwater can buffer negative effects of summer drought on tree growth. Therefore, in the face of the ongoing climate change and more frequent occurrence of extreme drought events, we recommend that groundwater extraction from floodplain forests should be reduced rather than increased to maintain tree vitality in the long term.